PATHOPHYSIOLOGICAL MECHANISMS AND CLINICAL SIGNIFICANCE OF HYPOTHYROIDISM - Sharofiddinov Javlon Komoliddinovich; Ikromova Dilnura Dilmurodovna (TADQIQOTLAR, 2026)
Abstract: Hypothyroidism is a common endocrine disorder characterized by a deficiency of thyroid hormones. According to current data, overt hypothyroidism occurs in approximately 0.3–5% of the general population, while subclinical hypothyroidism is found in about 4–10%, reaching up to 12% in some populations. It is observed more frequently among women and elderly individuals.This condition affects the body by disrupting metabolism, cardiovascular function, nervous system activity, digestive processes, and reproductive function. Hypothyroidism often develops slowly and insidiously, which may delay its early diagnosis. If not identified and treated in time, it can lead to serious complications such as myxedema, infertility, atherosclerosis, heart failure, and cognitive impairment. Therefore, studying the pathophysiological mechanisms and clinical significance of hypothyroidism is of great importance in modern medicine.